Species and functional diversity of direct‐seeded vegetation declines over 25 years. (10th January 2023) - Atkinson, Joe; Simpson‐Young, Charlotte; Fifield, Graham; Schneemann, Barton; Bonser, Stephen P.; Moles, Angela T.
Summary: The re‐establishment of native vegetation on disturbed land has been adopted widely as a form of ecological restoration in the past few decades. It is often suggested that establishing native plantings will lead to increasing biodiversity at restoration sites over time. However, this prediction has not been tested over long periods. Now that some pioneering projects and monitoring programs have become older, it is possible to quantify the long‐term benefits of native vegetation plantings. We asked how the plant diversity and function of 12 biodiverse native vegetation plantings has changed over approximately 30 years. We found that sites declined in measures of functional and species diversity over time. Shorter‐statured woody species were not as common at older sites. Surprisingly, sites initially seeded with a greater richness of species did not have higher standing richness at any later census period. While all sites produced net native biodiversity benefits relative to the exotic pastures they replaced, ongoing management and monitoring will be needed to ensure they continue to do so. Understanding the relationship between ageing native vegetation plantings and other components of the ecosystem (e.g., mammals, birds, invertebrates, soil, microorganisms) is a priority. Our results suggest that recruitment barriers in ex‐agricultural ecosystems are high and that the biodiversity benefits provided by shorter‐lived species will only be transient without ongoing management of these systems. Research confronting these recruitment barriers is a priority, and managers (and funders) of these kinds of restoration projects may need to be prepared for ongoing management of sites to promote lost components if they are desired as continual features of these ecosystems.